Penyuluhan Pelayanan Radiologi Di Dusun Parangloe Desa Batumalonro Kecamatan Biring Bulu Kabupaten Gowa - Sumarsono Sumarsono; Indah Musdalifa; Nurul Jannah (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2020)
Abstract The Community service activities in the form of counseling by a team from the Radiology Study Program of Poltekkes Muhammadiyah Makassar were carried out in early February 9, 2020, located in dusun Parangloe Desa Batumalonro Kecamatan Biring Bulu Kabupaten Gowa. Presentation on the Radiology Services Procedure was one way to introduce Radiology Services to the public including service procedures, radiation safety and service affordability. This is important because the Radiology Service has not been very popular among the people and there is still a negative stigma about the dangers of radiation and service costs. Several obstacles encountered during the radiology service counseling were (1) There were limitations in supporting facilities for conducting socialization and presentation, including the absence of a projector LCD. (2) Extension activities are not optimal during the day because they are bumped into the activities of the participants who are mostly farmers, where their activities start in the morning. The results of community service in February in the form of Counseling in Radiology Services in Dusun Parangloe Desa Batumalonro Kecamatan Biring Bulu Kabupaten Gowa have made a significant contribution to the understanding of the community in the field of radiology services, reflected in the enthusiasm of the community attending and engaging in discussions in Health counseling